Heat Storage: A Unique Solution For Energy Systems - Dincer, Ibrahim (Green Energy and Technology,, 2018)
This book covers emerging energy storage technologies and material characterization methods along with various systems and applications in building, power generation systems and thermal management. The authors present options available for reducing the net energy consumption for heating/cooling, improving the thermal properties of the phase change materials and optimization methods for heat storage embedded multi-generation systems. An in-depth discussion on the natural convection-driven phase change is included. The book also discusses main energy storage options for thermal management practices in photovoltaics and phase change material applications that aim passive thermal control. This book will appeal to researchers and professionals in the fields of mechanical engineering, chemical engineering, electrical engineering, renewable energy, and thermodynamics. It can also be used as an ancillary text in upper-level undergraduate courses and graduate courses in these fields.